Pengaruh Penerapan Somatis, Auditori, Visual, dan Intelektual Terhadap Kemampuan Komunikasi Matematis Siswa - Nujha Nirwana; Elly Susanti; Djoko Susanto (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2021)
Mathematical communication is very important to be considered in learning mathematics so that students are able to achieve the objectives of learning mathematics. Students must be able to communicate their thoughts and feelings through clear and correct spoken language. This study aims to determine the application of the SAVI learning model to improve students' mathematical communication. This study uses the library research method (library research), while data collection is done by searching for information, analyzing and concluding data by examining several journals, books, articles and notes related to the SAVI learning model and mathematics learning. The results of this study are mathematical communication in mathematics learning can be done with the SAVI model as an alternative in solving the difficulties faced by students. Somatic intelligence can direct students in learning mathematics that is seen and heard through body demonstrations or kinesthetic abilities. Auditory learners are able to listen in detail on topics in mathematics learning and express what they hear. Visual learners will be more active by discussing kalam material through videos, pictures, doodling, illustrations and colors. Intellectual learners are able to cover all previous intelligences, so learners are able to ask questions, story telling and problem solving. Komunikasi matematis sangatlah penting untuk diperhatikan dalam pembelajaran matematika agar siswa mampu mencapai tujuan pembelajaran matematika. Siswa harus mampu mengomunikasikan pikiran dan perasaan lewat bahasa lisan yang jelas dan benar. Penelitian ini bertujuan untuk mengetahui penerapan model pembelajaran SAVI (Somatis, Auditori, Visual, Intelektual), untuk meningkatkan komunikasi matematis siswa. Penelitian ini menggunakan metode library research (penelitian kepustakaan), sedangkan pengumpulan data dengan mencari informasi, menganalisa, dan menyimpulkan data dengan menelaah beberapa jurnal, buku, artikel serta catatan terkait dengan model pembelajaran SAVI dan pembelajaran matematika. Adapun penerapan dari SAVI pada komunikasi matematis di pembelajaran matematika dapat dilakukan dengan model SAVI yang merupakan alternatif dalam menyelesaikan kesulitan yang dihadapi siswa. Kecerdasan somatis dapat mengarahkan siswa dalam pembelajaran matematika yang dilihat dan didengar melalui peragaan tubuh atau kemampuan kinestis. Pembelajar auditori mampu mendengarkan secara detail topik pada pembelajaran matematika dan mengutarakan sesuatu yang didengar. Pembelajar visual akan lebih aktif dengan pembahasan materi melalui video, gambar, doodling, ilustrasi, serta warna. Pembelajar intelektual mampu meng-cover semua kecerdasan sebelumnya, maka pembelajar mampu untuk tanya jawab, strory telling, dan pemecahan masalah.